2020
DOI: 10.1136/bmjopen-2020-037045
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and epidemiological characteristics of inmates diagnosed with infectious diseases living in a region with a high number of prisons in São Paulo state, Brazil

Abstract: ObjectiveTo determine the prevalence and epidemiological characteristics of inmates diagnosed with infectious diseases living in a region with a high number of prisons, São Paulo, Brazil.DesignThis is a retrospective and descriptive study conducted from November 2017 to October 2018.SettingPrisons located in the western and northwestern regions of São Paulo, Brazil.MethodsWe conducted a retrospective analysis on infectious diseases and coinfections (HIV, hepatitis B virus (HBV), hepatitis C virus (HCV), syphil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 19 publications
0
26
0
1
Order By: Relevance
“…Prisoners with no history of institutional education (illiterate) were mentioned by nine articles, and the rate of complete illiteracy among participants ranged from 1.5% to 30.9%. 3 , 14 , 16 , 18 , 24 , 25 , 27 , 39 , 43 In addition, eight articles reported that their sample participants had only completed high school education, with a percentage ranging from 9.32% to 60%. 3 , 15 , 16 , 19 , 24 , 26 , 31 , 34 , 44 Finally, only eight studies reported higher educational levels among their participants, and reported university/college education from a low of 2.5% to a peak of 16.7%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prisoners with no history of institutional education (illiterate) were mentioned by nine articles, and the rate of complete illiteracy among participants ranged from 1.5% to 30.9%. 3 , 14 , 16 , 18 , 24 , 25 , 27 , 39 , 43 In addition, eight articles reported that their sample participants had only completed high school education, with a percentage ranging from 9.32% to 60%. 3 , 15 , 16 , 19 , 24 , 26 , 31 , 34 , 44 Finally, only eight studies reported higher educational levels among their participants, and reported university/college education from a low of 2.5% to a peak of 16.7%.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 14 , 16 , 18 , 24 , 25 , 27 , 39 , 43 In addition, eight articles reported that their sample participants had only completed high school education, with a percentage ranging from 9.32% to 60%. 3 , 15 , 16 , 19 , 24 , 26 , 31 , 34 , 44 Finally, only eight studies reported higher educational levels among their participants, and reported university/college education from a low of 2.5% to a peak of 16.7%. 14 , 16 , 17 , 21 , 24 , 34 , 43 , 44 One study reported that, more than 58% had of their participants' high education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WHO estimated that in 2016, approximately 399 000 people died from hepatitis C, mostly from cirrhosis and hepatocellular carcinoma (primary liver cancer). In Brazil, prevalence varies from 0.2% to 47% according geographical region or the group evaluated, such as drug users, inmates, Amerindians, people living with HIV, patients with hematological disorders, and chronic kidney disease patients 15‐18 . Kandeel et al 19 have evaluated the potential of antiviral drugs used for hepatitis C, like sofosbuvir, and daclatasvir, to build a model for COVID‐19 treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, prevalence varies from 0.2% to 47% according geographical region or the group evaluated, such as drug users, inmates, Amerindians, people living with HIV, patients with hematological disorders, and chronic kidney disease patients. [15][16][17][18] Kandeel et al 19 have evaluated the potential of antiviral drugs used for hepatitis C, like sofosbuvir, and daclatasvir, to build a model for COVID-19 treatment. In addition, it was observed fulminant outcome or reactivation of hepatitis infection during hepatitis B and COVID-19 coinfection.…”
mentioning
confidence: 99%